The Effect of Innovation Climate and Collaborative Learning on the Performance of Elementary School Teachers in Kelapa Dua District, Tangerang Regency - Mutiara Sambella; M Syadeli Hanafi; Sholih (Yayasan Payungi Smart Madani, 2025)
This study investigates the influence of training and professional competence on the quality of learning, while examining the mediating role of work culture among teachers in Madrasah Aliyah (MA) in the Walantaka sub-district. An explanatory quantitative research design was employed, using a closed-ended questionnaire administered to 71 respondents selected through a total sampling technique. Data were analyzed using path analysis with SPSS 26 to evaluate the direct and indirect effects of the variables. The findings reveal that training has a significant positive direct effect on learning quality (path coefficient = 0.261, p = 0.022, t = 4.730). Professional competence also demonstrates a significant direct effect (path coefficient = 0.208, p = 0.046, t = 3.656). Furthermore, work culture significantly enhances the quality of teacher learning (path coefficient = 0.342, p = 0.003, t = 5.404). Training indirectly influences learning quality through work culture, as confirmed by a Sobel t-value of 2.484, while professional competence does not exhibit a significant indirect effect (Sobel t = 1.392). Collectively, training, professional competence, and work culture account for 49.9% of the variance in work behavior, with the remaining 50.1% explained by other factors not included in this study. This research contributes to the literature on teacher professional development by demonstrating the critical role of work culture as a mediating factor that strengthens the impact of training on learning quality. The findings provide practical implications for educational policymakers and school leaders in designing training programs and fostering positive organizational cultures to enhance teacher performance and learning outcomes.